Whole-genome sequencing revealed concurrent outbreaks of shigellosis in the English Orthodox Jewish Community caused by multiple importations of Shigella sonnei from Israel. Issue 3 (27th March 2018) - Rew, Vanessa; Mook, Piers; Trienekens, Suzan; Baker, Kate S.; Dallman, Timothy J.; Jenkins, Claire; Crook, Paul D.; Thomson, Nicholas R.
Abstract : In December 2013, Public Health England (PHE) observed an increase in the number of cases of Shigella sonnei linked to the Orthodox Jewish Community (OJC). Ultimately, 52 cases of S. sonnei phage type (PT) P and PT7 were notified between November 2013 and July 2014. Whole-genome sequencing (WGS) was performed on a HiSeq 2500 platform (Illumina) on isolates of S. sonnei submitted to PHE during the investigation. Quality trimmed sequence reads were mapped to a reference genome using BWA-MEM, and single-nucleotide polymorphisms (SNPs) were identified using GATK2. Analysis of the core genome SNP positions (>90 % consensus, minimum depth 10×, MQ≥30) revealed that isolates linked to the outbreak could be categorized as members of distinct monophyletic clusters (MPCs) representing concurrent regional outbreaks occurring in the OJCs across the United Kingdom. A dated phylogeny predicted the date of the most recent common ancestor of the MPCs to be approximately 3.1 years previously [95 % highest posterior density (HPD), 2.4–3.4]. Isolates of S. sonnei from cases from the OJCs in Israel included in the phylogeny, branched from nodes basal to the UK OJC outbreak clusters, indicating they were ancestral to the UK OJC isolates, and that the UK isolates represented multiple importations of S. sonnei into the UK population from Israel. The level of discrimination exhibited by WGS facilitated the identification of clusters of isolates within the closely related bacterial populations circulating in the OJC that may be linked to a unique point sources or transmission routes, thus enabling a more appropriate public health response and targeted interventions.